Usage of 119 emergency medical services by pediatric patients during the COVID-19 pandemic: A characteristic analysis - Choi, Miyoung; Lee, Hyoju (Edelweiss Applied Science and Technology, 2025)
This study aimed to analyze the characteristics and trends in the use of 119 emergency medical services (EMS) by pediatric patients in Chungcheongnam-do, South Korea, during the COVID-19 pandemic to inform future EMS resource allocation. A retrospective analysis was conducted on emergency activity logs of 13,372 patients under 18 years of age transported by 119 ambulances from January 1, 2020, to December 31, 2021. The pandemic was divided into four phases for trend analysis. SPSS version 25 was used for statistical analysis. In 2020, EMS usage decreased to 6,112 cases, then increased to 7,260 in 2021. Patients under four primarily presented with respiratory symptoms, while older children mostly had musculoskeletal complaints. “Potentially urgent” was the most frequent severity level. Average prehospital time increased across pandemic phases, reaching 96 minutes in the fourth phase. Pediatric EMS usage patterns shifted during the pandemic, highlighting the need for adaptive EMS strategies. These findings provide foundational data to improve EMS preparedness and resource allocation in future infectious disease outbreaks.